Coffee Intake and Incidence of Erectile Dysfunction. Issue 5 (23rd August 2017) - Lopez, David S; Liu, Lydia; Rimm, Eric B; Tsilidis, Konstantinos K; de Oliveira Otto, Marcia; Wang, Run; Canfield, Steven; Giovannucci, Edward
Abstract: Coffee intake is suggested to have a positive impact on chronic diseases, yet its role in urological diseases such as erectile dysfunction (ED) remains unclear. We investigated the association of coffee intake with incidence of ED by conducting the Health Professionals Follow-Up Study, a prospective analysis of 21, 403 men aged 40–75 years old. Total, regular, and decaffeinated coffee intakes were self-reported on food frequency questionnaires. ED was assessed by mean values of questionnaires in 2000, 2004 and 2008. Multivariable adjusted Cox proportional hazards models were used to compute hazard ratios for patients with incident ED ( n = 7, 298). No significant differences were identified for patients with incident ED after comparing highest (≥4 cups/day) with lowest (0 cups/day) categories of total (hazard ratio (HR) = 1.00, 95% confidence interval (CI): 0.90, 1.11) and regular coffee intakes (HR = 1.00, 95% CI: 0.89, 1.13). When comparing the highest category with lowest category of decaffeinated coffee intake, we found a 37% increased risk of ED (HR = 1.37, 95% CI: 1.08, 1.73), with a significant trend ( P trend = 0.02). Stratified analyses also showed an association among current smokers ( P trend = 0.005). Overall, long-term coffee intake was not associated with risk of ED in a prospective cohort study.